Efficiency of shape memory alloy seismic restrainers for several conditions of bridge joints - Mohamed Hamdy El-Feky; Atef Eraky; Alaa M. Sharabash (Fracture and Structural Integrity)
Movement joints are needed in bridges to accommodate longitudinal expansion and contraction. Enough joint width needs to be available to accommodate not only longitudinal expansion but also expected movements of joints during earthquakes. This may result in excessive joint openings. Devices that can dissipate energy have been suggested to reduce joint displacements. Shape memory alloy (SMA) is one of these energy dissipation devices, which is well known for its ability to return to its natural shape after being deformed. Several cases of bridges and different conditions of seismic events are modeled and tested using developed software programs in MATLAB to show the efficiency of using SMA inside bridge joint openings. These models include the case of two adjacent frames with SMA inside them (2–frames), the case of multi–frames with constant hysteretic SMAs between every two of them (N–frames), the case of multi–frames with constant hysteretic SMAs taking the delay of seismic forces between frames into consideration (delay), and the case of variable masses of bridge frames. Also, parametric studies are performed to show the impacts of all parameters of bridge frames and SMA retrofit devices on seismically joint openings. The results show that the superelastic SMA device plays a huge role in controlling bridge opening and enables limiting the joint width of all models during earthquakes with different values reaching 60% in some cases depending on bridge frame properties, ground motion characteristics, and the hysteretic properties of SMA devices.